Cardiopulmonary Protection of Modified Remote Ischemic Preconditioning in Mitral Valve Replacement Surgery: A Randomized Controlled Trial - Lianqin Zhang; Kang Zhou; Tianchu Gu; Jingjing Xu; Mengzhu Shi; Jiang Zhu; Jindong Liu (Hindawi-Wiley, 2024)
Conclusions: mRIPC decreased the incidence of myocardial and lung injury in MVR surgery, providing new evidence for the clinical application of RIPC in valve surgery.